ANALISIS FAKTOR YANG MEMPENGARUHI LENGTH OF STAY (LOS) PADA PASIEN PEDIATRI DENGAN DIARE YANG MENDAPAT TERAPI ZINC DI RUMAH SAKIT X TAHUN 2023 - Rizka Ardita; Yane Dila Keswara; Fransisca Tri Wituningtyas (Jurnal Farmasi Indonesia, 2025)
Diarrhea is a significant contributor to child morbidity and mortality, with a prevalence of 10.2% in Indonesia. The purpose of this study is to examine factors affecting the length of stay (LOS) in pediatric diarrhea patients receiving zinc therapy at Hospital X in 2023. This was a retrospective observational study involving medical record analysis of 76 patients aged 0–18 years who met the inclusion criteria (diagnosed with diarrhea, received zinc therapy, and had complete data). Samples were selected using purposive sampling, with the minimum sample size calculated using the Lemeshow formula. Data were categorized based on the appropriateness of zinc dosage (10 mg/day for children <6 months and 20 mg/day for those ≥6 months) and duration of administration (10–14 days). Statistical analysis was performed using the Chi-Square test in SPSS version 26, with a significance level of p < 0.05. Results showed that 80.26% received the correct dose and 81.58% received zinc for the appropriate duration. There was a significant association between both zinc dosage (p = 0.012) and duration (p = 0.000) with LOS. This study highlights the importance of proper zinc therapy to shorten hospitalization in children with diarrhea.